KAJIAN APLIKASI EM- 4 DAN PUPUK GANDASIL D TERHADAP PERTUMBUHAN DAN PRODUKSI KANGKUNG ( Ipomoea reptana L. ) - Choirul Anam (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2017)
The increase in the production of sprouts can be carried out using the correct techniques of cultivation and fertilization, i.e. (timely, appropriate doses and on target) so that the results can be further maximized production in cultivation. The purpose of this research is to know the influence of the giving EM 4 and Gandasil D with different concentration towards growth and the production of plant water spinach (Ipomoea reptans L). Research methods include random design group (RAK) factorial consisting of 2 factors of treatment and three replicates: Factor I: concentration of EM4 with 3 levels: E1 = 5 ml. litre water ¹ ̄, E2 =: 10 ml. litre water ¹ ̄, E3:15 ml. litre water ¹ ̄. Factor II: concentration of Gandasil D with 3 levels namely: G1 = 1 g. liter water ¹ ̄, G2 = 3 g. liter ̄ ¹ air, G3 = 5 g. liter ̄ ¹ water. From the results it can be concluded that: 1. There is a concentration of treatment interactions granting EM 4 and Gandasil fertilizer on plant height of D at the age of 10 and 20 days after planting; the number of leaves at the age of 15 days after planting and 20; the number of shoots 10 days after planting; root length 30 days after planting; heavy plant persampel 30 days after planting. on treatment of the grant granting concentrations EM 4 (E2 = 10 ml. litre water ¹ ̄) and Gandasil D (G2 = 3 grams. ¹ ̄ litres water) or where the treatment the E2G2 gives the best results towards growth and the production of plant water spinach (Ipomoea reptana. L.); 2. There is a significant difference between the treatment of granting the concentration EM 4 and Gandasil D. plant age 15 and; the number of leaves at the age of 10 days after planting; on the number of shoots, there is the very real difference at age 15 days after planting, and different real at the age of 20 days after planting; 3. Combination treatment concentrations EM 4 (E2 = 10ml. iter ̄ ¹ water) and Gandasil D (G2 = 3 grams. ¹ ̄ litres water) or E2G2 best results towards growth and the production of plant water spinach (Ipomoea reptana. L.).